2020
DOI: 10.3390/ijms21155368
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Transcriptome Analysis of Niemann–Pick Disease, Type C1 Cerebella

Abstract: Niemann–Pick disease, type C1 (NPC1) is a lysosomal disease characterized by endolysosomal storage of unesterified cholesterol and decreased cellular cholesterol bioavailability. A cardinal symptom of NPC1 is cerebellar ataxia due to Purkinje neuron loss. To gain an understanding of the cerebellar neuropathology we obtained single cell transcriptome data from control (Npc1+/+) and both three-week-old presymptomatic and seven-week-old symptomatic mutant (Npc1−/−) mice. In seven-week-old Npc1−/− mice, differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 107 publications
(146 reference statements)
7
18
0
Order By: Relevance
“…As part of the NPC cerebellar inflammation signature, lysozyme, a highly conserved antibacterial hydrolase, is overexpressed [2][3][4][5]. Using single-cell RNAseq we found that Lyz2 was not only upregulated in microglia, as expected, but expression was also significantly increased in Npc1 −/− glial cells and neurons [6]. We proposed that elevated expression of lysozyme protein may functionally contribute to Purkinje neurons loss.…”
Section: Introductionsupporting
confidence: 63%
“…As part of the NPC cerebellar inflammation signature, lysozyme, a highly conserved antibacterial hydrolase, is overexpressed [2][3][4][5]. Using single-cell RNAseq we found that Lyz2 was not only upregulated in microglia, as expected, but expression was also significantly increased in Npc1 −/− glial cells and neurons [6]. We proposed that elevated expression of lysozyme protein may functionally contribute to Purkinje neurons loss.…”
Section: Introductionsupporting
confidence: 63%
“…To fully comprehend the genetic background of this association, future studies are warranted and scrutinizing the constitutive roles of genes—in particular, the 10 genes we identified—implicated in ferroptosis may help us understand the pathogenesis of many neurological diseases. Also, we expect that integrating single cell data in neurodegenerative disease models such as Niemann–Pick Disease, Type C1 [ 139 ] into this analysis will unveil ferroptosis genetic hallmarks under the neurological disease condition.…”
Section: Discussionmentioning
confidence: 99%
“…This will require a combination of preparations allowing to study the same type of cells in vivo, ex vivo, and in vitro (Figure 4) as well as new approaches to analyze mRNA, protein, and lipid content of defined cell types replacing transcriptomic, proteomic, and lipidomic studies of entire organs or tissues. As an example, acutely isolated cells combined with single cell transcriptomics [231] represent a first step that needs to be refined and extended with a focus on vulnerable cells in most affected organs, including the brain, liver, and lung. Cells differentiated from induced pluripotent stem cells represent an alternative although with caveats [397].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the outcome of a given mutation varies with the genetic background of strains [37,135,[215][216][217][218]. Numerous double mutant mice have been created to test whether and how specific candidate genes impact the disease [163,173,177,190,191,[219][220][221][222][223][224][225][226][227][228][229][230][231][232][233][234][235]. Sex-dependent differences in behavior [236], life span [37,134], and responses to immune activation [237] and to potential therapies [171,238] were reported in some NPC1 mutant mice, raising the question of whether sex is a modifying factor in NPC disease [37] as in other cholesterol-related pathologies [239][240][241][242] and normal cholesterol homeostasis [243,244].…”
Section: Mammalian Modelsmentioning
confidence: 99%